Hitting the bullseye: How does aggregate demand shape inflation targeting? - Yasin, Mohammad Zeqi; Adli, Fichrie Fachrowi (Jurnal Ekonomi Indonesia, 2025)
We aim to determine whether components of aggregate demand contribute to regional inflation reaching the threshold level. By using regional-level datasets of Indonesian cities from 2010 to 2023 with Logit and Tobit estimates, we reveal that the pandemic conditions influence the behaviour of aggregate demand components in achieving the inflation targeting level in cities. We show that household spending during the pandemic (in 2020 and afterwards) stimulates cities to reach the inflation targeting level. Likewise, gross fixed capital formation (GFCF) and government spending also increase the probability of the cities reaching inflation targets during the pandemic periods. However, there is no significant effect of exports during the pandemic in helping cities reach the inflation threshold. This finding is corroborated by the estimation of inflation gap reduction, where only household consumption, GFCF, and government spending contribute to the reduction of cities’ inflation gap towards the national targeting level. Our finding delivers policy implications, notably on how each city can achieve the national inflation targeting level.